Графическое представление функции принадлежности студентов к типологической группе в зависимости от успеваемости - Шевченко, В. А. (НТУ "ХПИ", 2015)
Сформулирована задача распределения студентов по типологическим группам как задача принятия решения в условиях неопределенности. Проведен обзор некоторых вариантов графического представления функций принадлежности, на основании чего функция принадлежности нечеткого множества студентов к определенной типологической группе в зависимости от успеваемости представлена в трапецеидальном виде. Определены значения функции принадлежности нечеткой функции перераспределения студентов в другую типологическую группу.

The aim of the article is to determine the value of the membership function of the fuzzy function of student redistribution into a different typological group based on the graphical representation of the results of student distribution into typological groups, depending on the academic performance. To achieve the assigned goal, there were used the methods of cluster analysis and the theory of fuzzy sets. The problem of student distribution into typological groups as a problem of decision-making under uncertainty is formulated. There was carried out a review of some embodiments of membership functions graphical representation, based on which the function of a fuzzy set of students belonging to a certain typological group, depending on the academic performance is presented in the form of a trapezoid. Based on the graphic representation of functions of a fuzzy set of students belonging to a typological group, depending on the academic performance, the quantitative values of student redistribution possibilities from one typological group into another were determined.
Graphical representation of the function of student typological group membership, depending on the academic performance
Keywords: функция принадлежности; нечеткое множество; типологическая группа; успеваемость студентов; графическое представление; fuzzy set; typological group; student performance; graphical representation; membership function